2021
DOI: 10.1371/journal.pone.0253526
|View full text |Cite
|
Sign up to set email alerts
|

A mixed method study design to explore the adherence of haematological cancer patients to oral anticancer medication in a multilingual and multicultural outpatient setting: The MADESIO protocol

Abstract: Background Patients with haematologic malignancies are increasingly treated by oral anticancer medications, heightening the challenge of ensuring optimal adherence to treatment. However, except for chronic myelogenous leukaemia or acute lymphoid leukaemia, the extent of non-adherence has rarely been investigated in outpatient settings, particularly for migrant population. With growing numbers of migrants in Belgium, identifying potential differences in drug use is essential. Also, previous research regarding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…13 Previous researches have shown that proper self-management of side effects, choosing drugs based on family economic conditions, age, and severity of disease all related to medication adherence. [14][15][16] However, these findings were all developed from the perspective of physicians, some important factors of medication adherence such as patients' perspectives about drug administration, family structure were generally overlooked. Drug adherence is a complex dynamic process of individual behavior, determined by multiple factors including treatment scheme, patients (eg, economic burden, cognitive ability, therapeutic attitude), and health-care providers (eg, doctors/nurses' reactions to therapy, society's perception of anticancer drug treatment).…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous researches have shown that proper self-management of side effects, choosing drugs based on family economic conditions, age, and severity of disease all related to medication adherence. [14][15][16] However, these findings were all developed from the perspective of physicians, some important factors of medication adherence such as patients' perspectives about drug administration, family structure were generally overlooked. Drug adherence is a complex dynamic process of individual behavior, determined by multiple factors including treatment scheme, patients (eg, economic burden, cognitive ability, therapeutic attitude), and health-care providers (eg, doctors/nurses' reactions to therapy, society's perception of anticancer drug treatment).…”
Section: Introductionmentioning
confidence: 99%